The impact of the COVID-19 quarantine on the estimated quality of parent-child interactions in Saudi Arabia: Parental perspectives - Alsari Nada Abdulkader (Psychology of Language and Communication)
The purpose of the current study was to explore parental beliefs about the effect of the COVID-19 quarantine on the subjectively estimated quality of parent-child interactions as well as their beliefs about its impact on early childhood language development within the Kingdom of Saudi Arabia (KSA). A cross-sectional observational study was conducted via an electronic survey. The study surveyed 439 parents of typical children aged between 24 and 60 months. The survey was distributed online to cover a wide range of participants across the KSA. Based on the parental subjective measure used in the current study, parent-child interactions and children's language skills had significantly increased during the quarantine (p < .001). In conclusion, the study highlighted the important role of parents during the critical period of language development in promoting their children's speech and language skills.